The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

Koala Conservation Policy Process: Appraisal and Recommendations - Tim W. Clark; Nicole Mazur; Steven J. Cork; Steve Dovers; Ronnie Harding (Conservation Biology, 2000)
Australia's koalas are a global treasure, yet there is growing concern that present policy may not adequately conserve viable, wild populations in abundant habitats. Problems in the content and particularly the process of policy making for koala conservation include integrating reliable knowledge and diverse perspectives. We reviewed the overall decision process involved in developing Koala conservation policy, including the functions of intelligence, promotion, prescription, invocation, application, appraisal, and termination. To date, intelligence ( planning ) has lacked social science data, and promotion (open debate) has been confrontational. Koala policy has been unclear about prescription (setting rules) and lacks specificity about needed standards, penalties for violating standards, and making resources available. Invocation and application (implementation) have been differentially successful. Appraisal has been adversarial and incomplete, and termination of weak practices has been difficult. We suggest implementation of procedural standards such as timeliness, comprehensiveness, and rationality for a better koala decision process. The 1998 National Koala Conservation Strategy and various state policies can be upgraded to meet these standards. Opportunities exist to improve koala management policy in all seven functions. We recommend a three‐part strategy: (1) identify, describe, and appraise successful conservation efforts to find the best practices, (2) disseminate success stories, and (3) open up new opportunities for improvement in all aspects of koala conservation.